The Understanding of Wasl Al-Fiqh Bi Al-Hadith at Traditional Dayah Aceh - lazuardi muhammad latif; Faisal Bin Ahmad Shah (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2021)
Wasl al-Fiqh bi al-Hadith integrates jurisprudence and hadith so that it enables fiqh experts to rely on hadith in formulating their rulings while hadith experts can derive a more accurate interpretation. Among others, this concept is applied at Aceh traditional dayah as the oldest Islamic educational institution in the Malay Archipelago which Acehness put their respect as the reference in Islamic rulings and teaching. This field study took place at Dayah Mudi Mesra, Samalanga, Aceh, due to its long-established reputation and great influence among Acehnese. The study aims to shed some light on the concept of wasl al-Fiqh bi al-Hadith according to some Islamic scholars, analyze the concept as perceived by the traditional Dayah of Aceh, and portray the polemic on Friday prayer ritual as prescribed by the traditional Dayah. The study employs qualitative data collection instruments consisting of library data, interviews, observations, and documentation. Inductive, deductive, and comparative methods were used for data analysis. The study found that implementation of this concept at the Dayah has been synonymous with the exclusive adoption of Shafi’i school as it heavily relies on several Shafi’i books or opinions of Shafi’i scholars as primary references.(Wasl al-Fiqh bi al-Hadith memadukan kajian fiqh dan hadis sehingga ahli fiqh dapat berpedoman kepada hadis dalam merumuskan aturan-aturan hukum sementara ahli hadis dapat mengetahui makna sebuah hadis dengan lebih akurat. Konsep ini salah satunya diterapkan di Dayah Tradisional Aceh, sebuah lembaga kajian Islam tertua di Kepulauan Melayu yang disegani dan menjadi rujukan dalam hal aturan serta ajaran Islam di masyarakat setempat. Kajian ini merupakan studi lapangan yang bertempat di Dayah Mudi Mesra Samalanga Aceh karena pengaruhnya yang sudah lama dan berakar kuat bagi masyarakat Aceh. Ia bertujuan mendalami konsep wasl al-fiqh bi al-hadith menurut para cendekiawan Muslim, mengkaji pemahaman akan konsep wasl al-fiqh bi al-hadith di kalangan Dayah tersebut dan memotret polemik soal pelaksanaan Salat Jumat di dalamnya. Kajian ini merupakan studi kualitatif dengan pengumpulan data secara pustaka, wawancara, observasi, dan dokumentasi. Sementara itu, analisis data dilakukan secara induktif, deduktif, dan komparatif. Hasil penelitian ini menunjukkan bahwa implementasi konsep tersebut sebenarnya tidak lebih dari adopsi eksklusif terhadap madzhab Syafi’i karena ketergantungan yang demikian kuat pada buku-buku madzhab Syafi’i serta pandangan ulama-ulama Syafi’iyyah sebagai referensi utama)